A Study on Investors’ Attitude towards Mutual Funds as an Investment Option - Singh, Binod Kumar (Journal of Asian Business Strategy, 2011)
In this paper, structure of mutual fund, operations of mutual fund, comparison between investment in mutual fund and bank and calculation of NAV etc. have been considered. In this paper, the impacts of various demographic factors on investors’ attitude towards mutual fund have been studied. For measuring various phenomena and analyzing the collected data effectively and efficiently for drawing sound conclusions, Chi-square (χ2) test has been used and for analyzing the various factors responsible for investment in mutual funds, ranking was done on the basis of weighted scores and scoring was also done on the basis of scale.